Characterization of the third SERK gene in pineapple (Ananas comosus) and analysis of its expression and autophosphorylation activity in vitro - Ma,Jun (2014)
Two somatic embryogenesis receptor-like kinase genes (identified as AcSERK1 and AcSERK2) have previously been characterized from pineapple (Ananas comosus). In this work, we describe the characterization of a third gene (AcSERK3) in this family. AcSERK3 had all the characteristic domains and shared extensive sequence homology with other plant SERKs. AcSERK3 expression was studied by in situ hybridization and quantitative real-time PCR to analyze its function. Intense in situ hybridization signals were observed only in single competent cells and competent cell clusters; no hybridization signal was detected in the subsequent stages of somatic embryogenesis. AcSERK3 was highly expressed in embryogenic callus compared to other organs, e.g., 20-80 fold more than in anther but similar to that of non-embryogenic callus, which was 20-50 fold that of anther. AcSERK3 expression in root was 80 fold higher than in anther and the highest amongst all organs tested. These results indicate that AcSERK3 plays an important role in callus proliferation and root development. His-tagged AcSERK3 protein was successfully expressed and the luminescence of His6-AcSERK3 protein was only ~5% of that of inactivated AcSERK3 protein and reaction buffer without protein, and 11.3% of that of an extract of host Escherichia coli pET-30a. This finding confirmed that the AcSERK3 fusion protein had autophosphorylation activity.